2016
DOI: 10.1186/s12913-016-1369-7
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the economic burden of Diabetes, TB and co-prevalence: evidence from Bishkek, Kyrgyzstan

Abstract: BackgroundThe increasing number of patients co-affected with Diabetes and TB may place individuals with low socio-economic status at particular risk of persistent poverty. Kyrgyz health sector reforms aim at reducing this burden, with the provision of essential health services free at the point of use through a State-Guaranteed Benefit Package (SGBP). However, despite a declining trend in out-of-pocket expenditure, there is still a considerable funding gap in the SGBP. Using data from Bishkek, Kyrgyzstan, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 46 publications
(59 reference statements)
2
45
0
Order By: Relevance
“…This accords with a study in central China by Yang and team (Yang, Li & Zheng, 2009). Management of DM is associated with long term financial burden (Arnold et al, 2016). Failure to cope with this heavy financial burden might be associated with psychological disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…This accords with a study in central China by Yang and team (Yang, Li & Zheng, 2009). Management of DM is associated with long term financial burden (Arnold et al, 2016). Failure to cope with this heavy financial burden might be associated with psychological disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Among those studies that found an association between coping strategy and socioeconomic status, poorer households are more likely to engage in detrimental coping strategies such as taking high-interest loans, sale of assets, withdrawing children from school and reducing food consumption, while wealthier households are more likely to rely on insurance, income or savings 8 25 28 29 47. (One study found that middle-class households were more likely to sell assets than poor or rich households 48…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of TB is 4 times greater in the DM population than in the general population [ 14 , 35 , 55 ]. Our study identified 6 studies that addressed quantitative estimates of active TB in diabetic individuals – 2 from China and 1 from each of the following countries: Bangladesh, Korea, Nepal, and Pakistan.…”
Section: Resultsmentioning
confidence: 99%